START and the Future of Deterrence - Mazarr, Michael J. author. aut Link
X, 257 p.
Keywords: Examining the future of nuclear deterrence in the 1990s and beyond, this book outlines aspects of the evolving strategic environment. It also projects the likely future of deterrence strategies and strategic force postures. Other topics, such as the Soviet nuclear doctrine are also covered.